Aboveground biomass in secondary montane forests in Peru: Slow carbon recovery in agroforestry legacies - Aragon, Susan (2021)
This work was supported by a CONCYTEC (Peru) -World Bank grant (Contract 011-2019-FONDECYT-BM-INC-INV). In Huayopata we thank the Cuba and Povea families for their hospitality and help during field work.